Improvement of roof shield design using TRIZ method - Hoh, Rui Bin; Nasrul Azuan, Alang; M. I., M. Ramli; J., Alias; A. M., Romy
Factors such as poor aerodynamic shape, rigid roof and lack of attractiveness are the few factors that need to be taken into consideration for the roof shield design of a utility motorcycle. The purpose of this study is to improve the current design of the roof shield using TRIZ tools and techniques. The current design has some limitations due to the inventive parameters conflict of each component and causes engineering contradiction. Therefore, the TRIZ method is employed as a method to eliminate those inventive limitations. Function analysis is chosen as the initial step to determine the involved components and the components that are needed in the system. TRIZ method with the use of causes-effects chain analysis (CECA) then is applied by building the problem chain to obtain the potential effective cause. Using this approach, the engineering contradiction of the roof shield component is identified. Next, 40 inventive principles matrix in TRIZ, is applied to obtain a potential solution to the contradiction. Further brainstorm then is carried out to improve the design based on trigger potential inventive solution. The final conceptual design is sketched out and it is found that the overall design of the roof shield is improved in term of aerodynamic, flexibility and attractiveness.